Postradical Hysterectomy Survival Rate in Early Stage Cervical Cancer Patients - Yeremia, Wesley; Rarung, Max; Laihad, Bismarck J (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: Determining the survival rate of early stage cervical cancer patients after radical hysterectomy. Method: A retrospective cohort study was conducted on 24 earlystage cervical cancer patients who had performed radical hysterectomy in Prof. dr. R.D. Kandou Hospital Manado during the period between January 2008 and December 2010. We used Kaplan-Meier methods to observe the survival rate. Result: The mean age of patients in this study was 47.8 (33-63) years old with a median of 45 years old. The largest proportion was less than 50 years old (66.7%) and stage IIA cervical cancer (66.7%) as the severity of cancer. Most histopathology type was the squamous cell carcinoma (50.0%). About 70.8% patients did not have lymph nodes metastasis and 62.5% patients did not receive adjuvant therapy. This study revealed that 1-year, 2-year, 3-year, 4-year, and 5-year survival rate were 100.0%, 100.0%, 95.8%, 83.0%, 70.8%; respectively. Conclusion: The survival rate of early stage cervical cancer afte[Indones J Obstet Gynecol 2016; 4-3: 164-169] Keywords: cervical cancer, radical hysterectomy, survival rate